APLIKASI PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN METODE VARIABLE COSTING PADA TOKO SINGAMAS TANJUNGPINANG - Yenni Ratnawati; Ade Winarni (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2019)
The cost of production has an important role in determining the selling price of a product produced by a business. In the cost of goods manufactured there are elements of costs that are charged to a product. The elements of these costs include raw material costs, direct labor costs and factory overhead costs. In addition, the cost of goods manufactured is also a useful tool for maintaining the viability of a business, because with the right calculation, the company can estimate the selling price accurately in order to make a profit. Toko Singamas is a shop that produces bread. In this thesis research, the writer wanted to build an Application of production cost calculation by full costing method and variable costing method at Toko Singamas Tanjungpinang. The goal is to try to provide an alternative with the method of full costing and variable costing is where the calculation of the cost of production of the company to be more accurate. Research methods include directly with observations and interviews, as well as indirectly with literature studies with relevant sources. The system development analysis starts from identifying the problem, collecting the required data, and making the appropriate information design. Followed by system design starting from model design, database normalization design, input output design, report design, up to the method of application. Software that is used as a tool in the design of applications such as Java Netbeans and MySQL-Front as a database. The results of this application analysis that is, can see the method of full costing and variable costing method where from the results can choose the method for calculation of the cost of production accordingly.